Brock biology of microorganisms - Madigan, Michael T.; Bender, Kelly S.; Buckley, Daniel H.; Sattley, W. Matthew; Stahl, David A. (Pearson Education, 2022)
"Teaches the principles of modern microbiology. Includes both historical background and foundational aspects of microbiology, as well as a robust and modern treatment of microbiology with concrete examples of the microbial world"-- Provided by publisher.